The Influence of Entrepreneurial Mindset, Entrepreneurship Motivation, and Risk Taking Propensity on Student Intention to Become an Entrepreneur in Students in Sukabumi City - Ajeng Marnisa Herlambang Sukma; R. Deni Muhammad Danial; Resa Nurmala (Universitas KH. Abdul Chalim Mojokerto, 2025)
Unemployment is considered a common problem in all countries. This can happen because of the increasing population or because people are not motivated to create their own jobs. Students have an active role in creating jobs and should have the motivation to become entrepreneurs. If these students have the motivation to develop their business and have a mindset about entrepreneurship, it can enable this generation to overcome concerns, by being ready to face challenges or risks that will be faced in the future in carrying out entrepreneurial activities. The purpose of this research is to determine the effect of entrepreneurial mindset, entrepreneurship motivation and risk taking propensity on students' intentions to become entrepreneurs. This research was conducted on students in the city of Sukabumi with a total of 240 students as respondents. The multiple linear regression analysis approach was used as a method for this research. The results of the study can be obtained based on SPSS calculations and research showing that entrepreneurial mindset has a positive and significant effect on students' intentions to become entrepreneurs. Entrepreneurship Motivation has a positive and significant effect on students' intentions to become entrepreneurs. Risk taking propensity has a positive and significant effect on students' intentions to become entrepreneurs.